解方程:5-(x-6.8)=12 7x+0.8x=9.36
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 14:15:18
解方程:5-(x-6.8)=127x+0.8x=9.36解方程:5-(x-6.8)=127x+0.8x=9.36解方程:5-(x-6.8)=127x+0.8x=9.365-(x-6.8)=125-x+
解方程:5-(x-6.8)=12 7x+0.8x=9.36
解方程:5-(x-6.8)=12 7x+0.8x=9.36
解方程:5-(x-6.8)=12 7x+0.8x=9.36
5-(x-6.8)=12
5-x+6.8=12
x=12-5-5.8
x=1.2
7x+0.8x=9.36
(7+0.8)x=9.36
7.8x=9.36
x=9.36÷7.8
x=1.2
5-(x-6.8)=12
5-x+6.8=12
-x=12-5-6.8
-x=0.2
x=-0.2
7x+0.8x=9.36
7.8x=9.36
x=1.2
解方程:5-(x-6.8)=12 7x+0.8x=9.36
解方程.(5x/x²+x-6)+(2x-5/x²-x-12)=7x-10/x²-6x+8
X-X/12-X/7-X/8-X/4-X/20-X/5-30-120-300=50解方程
解方程:5x+x=12
1/x²-3x+2+1/x²+5x+6+1/x²+7x+12=1/3x 解方程 ( 用部分分式)
1x+2x+3x+4x+5x+6x+7x+8x+9x+10x+11x+12x+13x+14x+15x=550必须用解方程
解方程 x(2x-5)=4x-10 x+5x+7=3x+11
解方程:6x(7-x)=36-2x(3x-5)x是字母x
解方程:x(3x-4)+2x(x+7)=5x(x-7)+90
解方程:5x(x+7)(x+4)=5x(x的平方+11x)
5x(x+7)(x+4)=5x(x^2+11X)解方程,
解分式方程(5-2x)/(x^2-x-12)=5x/(x^2+x-6)+(10-7x)/(x^2-6x+8)得
解方程x²+x-6分之5x+x²-x-12分之2x-5=x²-6x+8分之7x-10
解方程:2(X-3)(X+5)=X平方+(X+2)(X-2)+(X+7)
12+x/(5+x)=12/7 解方程
解方程:7x/(5x+12)=9/7
解方程:3x+9=6x-12 9x-12-7x=5
解方程:3x+9=6x-12 9x-12-7x=5